Chapter Nature protection and local development: a study concerning a natural park located in Sardinia (Italy) - Marras, Martina (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Regional natural parks can include areas having high natural and environmental values. Defining appropriate spatial planning tools for these areas is therefore of outmost importance to protect the ecological balance and to promote social and economic development. The Tepilora Natural Park, in Sardinia, represent a relevant case study to deal with this problematic dichotomy. The study implements a knowledge-based planning methodology that, starting from an in-depth analysis of the context, identifies a territorial system characterized by sub-areas to be assigned a specific level of protection.